2014
DOI: 10.3109/15368378.2014.919588
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic field increases survival rate of dental pulp stem cells during DMSO-free cryopreservation

Abstract: Successful and efficient cryopreservation of living cells and organs is a key clinical application of regenerative medicine. Recently, magnetic cryopreservation has been reported for intact tooth banking and cryopreservation of dental tissue. The aim of this study was to assess the cryoprotective effects of static magnetic fields (SMFs) on human dental pulp stem cells (DPSCs) during cryopreservation. Human DPSCs isolated from extracted teeth were frozen with a 0.4-T or 0.8-T SMF and then stored at -196 °C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
2
27
0
1
Order By: Relevance
“…They suggested that the cryoprotective effect of static MFs is not because of MF effects on water molecules, but to enhanced biophysical stability of the cell membrane that reduces dehydration damage during freezing. Similar results and conclusions were found by Lin and others () after freezing dental pulp stem cells in static MFs of 400 and 800 mT.…”
Section: Experimental Data About the Effects Of Mfs On Freezingsupporting
confidence: 91%
See 2 more Smart Citations
“…They suggested that the cryoprotective effect of static MFs is not because of MF effects on water molecules, but to enhanced biophysical stability of the cell membrane that reduces dehydration damage during freezing. Similar results and conclusions were found by Lin and others () after freezing dental pulp stem cells in static MFs of 400 and 800 mT.…”
Section: Experimental Data About the Effects Of Mfs On Freezingsupporting
confidence: 91%
“…To do so, it is necessary to evaluate magnetic effects not only in water but also in other molecules that could be affected by MFs. Thus, as mentioned before, Lin and others (,b, ) have already pointed out the role that phospholipids could play in the cryoprotective effect of static MFs. Moreover, Kobayashi and Kirschvink () suggested that the presence of ferromagnetic materials in biological tissues, principally biologically precipitated magnetite (Fe 2 O 4 ), could be relevant to inhibit ice nucleation.…”
Section: Key Considerations and Needs For Future Researchmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the optimum SMF magnitude to promote cell proliferation is yet to be determined. Lew et al () demonstrated that 0.4‐T SMF significantly enhanced the proliferation of DPSCs (Lin et al, ). It was also reported that 60 and 120 μT of SMF could promote the proliferation of endothelial cells (Martino, Perea, Hopfner, Ferguson, & Wintermantel, ).…”
Section: Discussionmentioning
confidence: 91%
“…Bondemark et al () indicated that there are no changes in human dental pulp or gingival tissue adjacent to the magnet implants. Lew et al () and Lin et al () reported that 0.4‐Tesla (T) SMF promotes DPSCs proliferation. A 0.29‐T SMF does not influence the cell cycle and proliferation but accelerate the osteogenic differentiation and mineralization of dental pulp cells (Hsu & Chang, ).…”
Section: Introductionmentioning
confidence: 99%